Enantioselective synthesis of syn/anti-1,3-amino alcohols via proline-catalyzed sequential alpha-aminoxylation/alpha-amination and horner-wadsworth-emmons olefination of aldehydes - Jha, Vishwajeet; Kondekar, Nagendra B.; Kumar, Pradeep (Organic Letters, 2010)
A novel and general method for asymmetric synthesis of both syn/anti-1,3-amino alcohols is described. The method uses proline-catalyzed sequential alpha-aminoxylation/alpha-amination and Horner-Wadsworth-Emmons (HWE) olefination of aldehydes as the key step. By using this method, a short synthesis of a bioactive molecule, (R)-1-((S)-1-methylpyrrolidin-2-yl)-5-phenylpentan-2-ol, is also accomplished.

Proline-catalyzed asymmetric synthesis of syn- and anti-1,3-diamines - Kumar, Pradeep; Jha, Vishwajeet; Gonnade, Rajesh G. (Journal of Organic Chemistry, 2013)
A general organocatalytic strategy for asymmetric synthesis of both syn/anti-1,3-diamines has been developed. The strategy employs proline-catalyzed sequential alpha-amination and Horner-Wadsworth-Emmons (HWE) olefination of aldehydes as the key step where syn-1,3-diamine was obtained as the most favorable product.

Synthesis of indolizidine, pyrrolizidine and quinolizidine ring systems by proline-catalyzed sequential alpha-amination and HWE olefination of an aldehyde - Kauloorkar, Shruti Vandana; Jha, Vishwajeet; Kumar, Pradeep (RSC Advances, 2013)
A general procedure for the synthesis of azabicyclic ring systems viz. indolizidine, pyrrolizidine and quinolizidine has been developed utilizing proline-catalyzed sequential alpha-amination and Horner-Wadsworth-Emmons (HWE) olefination of an aldehyde as the key step. This method can be further extended to the synthesis of various biologically active natural products containing azabicyclic ring systems.

Croncise organocatalytic route to protected (2S, 4R)-4-hydroxyornithine and(+)-pseudohygroline - Jha, Vishwajeet; Kumar, Pradeep (Synlett, 2014)
A practical, efficient, and organocatalytic approach to the synthesis of (2S,4R)-4-hydroxyornithine and (+)-pseudohygroline is reported using proline-catalyzed sequential alpha-aminoxylation/alpha-amination reaction and Horner-Wadsworth-Emmons olefination reaction of an aldehyde as the key step.
Keywords: aldehydes; Amination; Amino alcohols; cyclization; Enantioselectivity; Wittig reaction

Organocatalytic stereoselective approach to the total synthesis of (-)-halosaline - Jha, Vishwajeet; Kumar, Pradeep (RSC Advances, 2014)
A practical and efficient organocatalytic approach to the synthesis of substituted piperidine alkaloids in high enantio- and diastereomeric excess was achieved using proline-catalyzed sequential alpha-aminoxylation/alpha-amination reaction and HWE olefination reaction of an aldehyde.

Stereoselective approach to 2,6-disubstituted piperidin-3-ol: synthesis of (-)-deoxoprosopinine and (+)-deoxoprosophylline - Jha, Vishwajeet; Kauloorkar, Shruti Vandana; Kumar, Pradeep (European Journal of Organic Chemistry, 2014)
A simple and highly efficient approach to an enantioenriched 2,6-disubstituted piperidin-3-ol skeleton is developed from an aldehyde as a starting material by using organocatalytic and asymmetric dihydroxylation as the key steps. Its application to the total synthesis of (-)-deoxoprosopinine and (+)-deoxoprosophylline is also reported.
Keywords: alkaloids; Amination; Amino alcohols; synthetic methods; Wittig reactions

Stereoselective approach to indolizidine and pyrrolizidine alkaloids: total synthesis of (-)-lentiginosine, (-)-epi-lentiginosine and (-)-dihydroxypyrrolizidine - Kauloorkar, Shruti Vandana; Jha, Vishwajeet; Jogdand, Ganesh F.; Kumar, Pradeep (Organic & Biomolecular Chemistry, 2014)
A simple and highly efficient approach to hydroxylated pyrrolizidine and indolizidine is developed from an aldehyde as a starting material using organocatalytic and asymmetric dihydroxylation reactions as key steps. Its application to the total synthesis of (-)-lentiginosine, (-)-epi-1,2-lentiginosine and (-)-dihydroxypyrrolizidine is also reported.

Modular synthesis of biaryl-substituted phosphine ligands: application in microwave-assisted palladium-catalyzed C-N cross-coupling reactions - Singh, Chandani; Rathod, Jayant; Jha, Vishwajeet; Panossian, Armen; Kumar, Pradeep; Leroux, Frederic R. (European Journal of Organic Chemistry, 2015)
Biaryl-substituted monophosphine-based ligands have been synthesized by transition-metal-free ARYNE cross-coupling reaction of aryllithiums with 1,2-dibromobenzene and subsequent regioselective functionalization through bromine-lithium interconversion. These ligands were employed in palladium-catalyzed C-N bond-forming reactions. The reaction was found to be general with wide substrate applicability. A wide variety of both primary and secondary amines were successfully coupled with an array of differently substituted halobenzenes under microwave irradiation to give the expected products in good to excellent yields. A number of biaryl-substituted phosphine ligands screened for the coupling reaction showed that steric bulk and the electronic properties of substituents on phosphorus play a crucial role in governing the catalytic activity of C-N cross-coupling reactions.
Keywords: Biaryls; Cross-coupling; Homogeneous catalysis; Microwave chemistry; Palladium; Phosphines; synthetic methods

Stereocontrolled synthesis of Hagen's gland lactones via iterative proline catalyzed alpha-aminoxylation and oxa-Michael addition reactions - Kauloorkar, Shruti Vandana; Jha, Vishwajeet; Jogdand, Ganesh F.; Kumar, Pradeep (RSC Advances, 2015)
A simple and efficient synthesis of Hagen's gland lactones was achieved using a sequential alpha-aminoxylation/oxa-Michael approach in a highly diastereoselective manner with assignment of relative configurations. This method was found to be applicable to the synthesis of various other isomers of Hagen's gland lactones.